Adsorption of Free Fatty Acids from Crude Palm Oil Using Calcium Silicate (CaSiO3) Adsorbent Glycerol Template - sembiring, seri bima; Siahaan, Ananda Putra (Talenta Publisher, 2023)
The adsorption of free fatty acids (FFA) in crude palm oil (CPO) using two types of adsorbents, namely Calcium Silicate (CaSiO3) template 5% glycerol (CTG5) and Calcium Silicate (CaSiO3) template 10% glycerol (CTG10). The experimental results showed that the titration method determined the decrease in FFA levels in CPO. This study used mass variations of adsorbent as much as 0.5 g, 1 g, and 1.5 g and agitation time (stirring) for 1, 3, 5, and 7 minutes. Based on the adsorption process, the most significant FFA adsorption results were obtained by using a CTG5 adsorbent with an adsorbent mass of 1.5 g and stirring time for 7 minutes at 80% with the weight of FFA adsorbed as much as 0.203 g FFA of 0.254 g FFA in 2 g of CPO.